الأدب الإسلامي قراءة في المفهوم وتأصيل المصطلح بين محمد إقبال العروي ونقاد آخرين (مجلة الواحات للبحوث والدراسات, 2021)
This Article Seeks To Read The Reception Of (Islamic Literature) In Modern Arab Criticism, In A Comparative View Of The Theses Of Muhammad Iqbal Alaraui, One Of The Most Interested In This Literary Trend; In The Second Half Of Last Century, The Authors Of This Literature Published A Large Number Of Creative And Critical Texts That Could Provoke Much Debate And Discussion. Arawi's Arguments Continued To Form A Critical And Theoretical Phenomenon. What Is The Position Of The Term (Islamic Literature) Of Dualism: Rejection And Acceptance? Throughout His Historic Procession? What Are The Arguments Of Alaraui And Those Who Have The Same Opinion Of Contemporary Critics? Key Words-Islamic Literature - Concept - Rooting – Alarawi.